Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Dan Kecerdasan Spiritual Terhadap Tingkat Pemahaman Akuntansi Pada Mahasiswa Aktif Program Studi S1 Akuntansi Universitas Hindu Indonesia - Ni Putu Ayu Diah Erikka; I Wayan Sudiana; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2026)
This study focuses on the relationship between intellectual, emotional, and spiritual intelligence and the level of accounting understanding among active accounting undergraduate students at Universitas Hindu Indonesia. It emphasizes how these aspects of intelligence shape students’ ability to comprehend accounting topics, along with providing empirical proof of these relationships. A student’s level of accounting understanding indicates how well accounting knowledge is comprehended, including theoretical ideas as well as real-world practice. The research uses a quantitative approach based on a sample of 228 respondents. Data processing involves testing for validity and reliability, followed by classical assumption analysis and multiple linear regression, including the determination of the coefficient of determination and the execution of both the F-test and t-test. Accounting understanding shows considerable improvement when supported by intellectual, emotional, and spiritual intelligence, both when assessed separately and as a whole. Accounting understanding is explained by three independent variables, contributing 51.6% of its variation, while other variables outside the research framework account for the remainder. Students are encouraged to increase learning effectiveness through active academic involvement, organizational engagement, and the development of emotional and spiritual dimensions.